Relation Between the SpvC and InvA Virulence Genes and Resistance of Salmonella enterica Serotype Enteritidis Isolated from Avian Material - Okamoto, Adriano Sakai; Filho, Raphael Lucio Andreatti; Rocha, Ticiana Silva; Menconi, Anita; Marietto-Goncalves, Guilherme Augusto (International Journal of Poultry Science, 2009)
Pathogenic bacteria possess genes responsible for virulence, that when expressed, determine not only bacterial invasion and persistence and destruction of host cells but also survival capacity under inappropriate culture conditions. This study utilized 100 samples of Salmonella enterica subspecies enterica Serotype Enteritidis (SE) isolated from avian material, detected the virulence genes InvA and SpvC by medium of Polymerase Chain Reaction (PCR) and compared them for possible expression of virulence factors for survival in hostile conditions of temperature, pH and reduced concentration of nutrients necessary for SE multiplication. Of all the samples analyzed, two presented the genes SpvC and InvA, simultaneously, with one probable expression of them being verified in growth with pH 10.0 or temperature of 25oC. But in relation to nutrient concentration, neither sample obtained growth when seeded in medium containing 0.5% nutrient.